Protocol for a Systematic Review of Telehealth Privacy and Security Research to Identify Best Practices - WATZLAF, VALERIE J.M. (Int J Telerehabil, 2015)
Healthcare professionals engaged in telehealth are faced with complex US federal regulations (e.g., HIPAA/HITECH) and could benefit from the guidance provided by best practices in Privacy and Security (P&S). This article describes a systematic review protocol to address this need. The protocol described herein uses the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols (PRISMA-P). The PRISMA-P contains 17 items that are considered essential, as well as minimum components to include in systematic reviews. PICOS (participants, interventions, comparisons, outcome(s) and study design of the systematic review) are also relevant to the development of best practices in P&S in telehealth systems. A systematic process can best determine what information should be included and how this information should be retrieved, condensed, analyzed, organized, and disseminated.